The results of the investigation of the β-casein gene polymorphism in sheep breed – Review - Nagy, Krisztina; Jávor, András; Kusza, Szilvia (Acta Agraria Debreceniensis, 2017)
β-casein is the most abundant protein fraction in sheep milk, and has at least six different alleles (A, B, C, G, X, Y). The alleles of the β-casein gene may influence on the quality and quantity of milk. Knowing the gene polymorphism has an important role in the process of milk production. The properties of milk could be positively influenced by themolecular genetic methods.